2009
DOI: 10.1111/j.1463-1318.2008.01743.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocutaneous flap reconstruction of the pelvis after abdominoperineal excision

Abstract: Data from the controlled studies support the use of myocutaneous flaps for single-stage reconstruction after APE in the presence of chemoradiotherapy. Ultimately, the choice of flap depends on the goals of reconstruction, size of the defect and the availability of donor tissue. The implications of an expanding role for radiotherapy in the treatment of low rectal cancer and radical dissection to achieve negative circumferential margins, necessitate close co-operation between colorectal and reconstructive surgeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
88
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(96 citation statements)
references
References 45 publications
4
88
1
3
Order By: Relevance
“…Myocutaneous flaps are one possible solution for reduction of perineal wound related complications, yet they add significantly to the duration of the procedure and all carry the risk of longer bed rest, flap-related complications and donor site morbidity. 5,31 Our study adds to the work of other groups on biologic grafts for repair of large perineal wounds 32,33 and indicates that good outcomes can be obtained without the addition of a flap procedure.…”
Section: Vaughan-shaw King Cheung Beck Knight Nichols Nugent Pilkingtmentioning
confidence: 52%
“…Myocutaneous flaps are one possible solution for reduction of perineal wound related complications, yet they add significantly to the duration of the procedure and all carry the risk of longer bed rest, flap-related complications and donor site morbidity. 5,31 Our study adds to the work of other groups on biologic grafts for repair of large perineal wounds 32,33 and indicates that good outcomes can be obtained without the addition of a flap procedure.…”
Section: Vaughan-shaw King Cheung Beck Knight Nichols Nugent Pilkingtmentioning
confidence: 52%
“…It has been shown that a non-healing wound can complicate an APR in up to 51% of patients. 9 Bullard et al reported a major wound complication rate of 35% out of 160 APR patients. 10 These results have meant that advancements in surgical technique have been necessary to improve wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Nisar and Scott reported 10 fascial dehiscences in 385 patients. 9 This gave a dehiscence rate of 2%. Others have reported rates of between 0% and 11%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Skin-muscle flap of the gluteus maximus muscle, skin-muscle-fascia flap of the thin thigh muscle (gracilis muscle) and transfer vertical skin-muscle flap of the abdominal rectus muscle are used most commonly [3,[5][6][7]. Application of the gracilis muscle as a basis of the skin-muscle-fascia transfer flaps with axial blood supply is favored by an easy access for harvesting, the possibility of bilateral plasty, if necessary, and minimal early and late complications at the site of the donor area [4].…”
mentioning
confidence: 99%